Analisis wacana nilai pendidikan multikultural dalam buku teks Sejarah Indonesia kelas XI sekolah menengah atas kurikulum merdeka - Dwi Wahyu Ningtyas; Dewa Agung Gede Agung; Moch. Nurfahrul Lukmanul Khakim (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2022)
This article aims to describe and analyze the discourse on the value of multicultural education in the Indonesian History textbook for Class XI Senior High School Curriculum Merdeka. This article uses a qualitative approach using the critical discourse analysis method of Norman Fairclough's model. The source of the data in this study was the Indonesian History textbook Independent Curriculum for class XI published by the Center for Curriculum and Books (Kemendikbudristek). Collecting data in this study using documentation study techniques. The way to do this is by collecting qualitative documents, both in the form of public documents and private documents. Then the researcher conducted a text analysis by examining the implied meaning in the textbook. The data analysis technique in this study follows the critical discourse analysis technique of Norman Fairclough's model, which consists of textual analysis of description, interpretation, and explanation. The results obtained from this study, namely the fact that in the Indonesian History textbook for Class XI Senior High School Curriculum Merdeka, the value of multicultural education that most often appears is the responsibility of the world community with multicultural indicators, namely collaborating in social activities regardless of cultural differences. The percentage of multicultural education values that appear in the entire Indonesian History textbook are human values 29 percent, democratic values 28 percent, plurality values 18 percent, divine value 11 percent, justice values 9 percent, and tolerance values 5 percent. Artikel ini bertujuan untuk mendeskripsikan dan menganalisis wacana nilai pendidikan multikultural dalam buku teks Sejarah Indonesia Kelas XI Sekolah Menengah Atas Kurikulum Merdeka. Artikel ini menggunakan pendekatan kualitatif dengan menggunakan metode analisis wacana kritis dari model Norman Fairclough. Sumber data dalam penelitian ini adalah buku teks Sejarah Indonesia Kurikulum Merdeka untuk kelas XI yang diterbitkan oleh Pusat Kurikulum dan Perbukuan (Kemendikbudristek). Pengumpulan data dalam penelitian ini menggunakan teknik studi dokumentasi. Cara yang dilakukan yakni dengan mengumpulkan dokumen kualitatif, baik berupa dokumen publik maupun dokumen privat. Kemudian peneliti melakukan analisis teks dengan mengkaji makna yang tersirat dalam buku teks. Teknik analisis data dalam penelitian ini mengikuti teknik analisis wacana kritis model Norman Fairclough, yang terdiri dari analisis teks deskripsi, interpretasi, dan eksplanasi. Hasil yang diperoleh dari penelitian ini yakni didapatkan fakta bahwa buku teks Sejarah Indonesia Kelas XI Sekolah Menengah Atas Kurikulum Merdeka, nilai pendidikan multikultural yang paling sering muncul adalah tanggung jawab masyarakat dunia dengan indikator multikultural yakni bekerjasama dalam kegiatan sosial tanpa memandang perbedaan budaya. Presentase jumlah nilai pendidikan multikultural yang muncul dalam keseluruhan buku teks Sejarah Indonesia nilai kemanusiaan 29 persen, nilai demokratis 28 persen, nilai pluralitas 18 persen, nilai keutuhan 11 persen, nilai keadilan 9 persen, dan nilai toleransi 5 persen.